The Impact Of Application Of Financial Management Bases On Development Non-Governmental Organizations Performance Efficiency In Syria - الحكيم, سلمان (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aims to know the application degree of financial management bases in Syrian development non-governmental organizations, and to know the impact level that application on performance efficiency in those organizations. Wherefore, the researcher has deduced the bases of financial management in NGOs by studying and analyzing the most important guides and instructions related to the financial management of NGOs. Therefore, the researcher has identified four bases of financial management of NGOs: planning and budgeting, accounts record-keeping, financial reporting and financial control. For realizing the aim of study, the researcher depended on questionnaire as a tool for collecting data, and distributed it to the organizations of study sample which amounted to (25) organizations. Analyzing data and testing hypothesis have been done by using SPSS program. According to the results of analysis, the level of application of financial management bases in Syrian development non-governmental organizations has been high relatively, and there has been a significant impact of financial management bases on performance efficiency in those organizations.